The activity of Terminalia chebula Retz. extract on doxorubicin-induced renal damage in rats. - Aamina Muneer; Ahmad Alhowail; Maha Aldubayan; Syed Imam Rabbani (GarVal Editorial Ltda., 2020)
Context: Doxorubicin (DXR) is a common anticancer drug known to produce several complications. Terminalia chebula popularly known as 'King of medicine' is found to possess wound healing, anti-inflammatory and antioxidant properties. Aims: To evaluate the effects of Terminalia chebula extract on doxorubicin-induced renal damages in rats. Methods: Coadministration of Terminalia chebula extract (0.25, 0.5 and 1.0 g/kg) was tested against DXR (2.5 mg/kg) induced renal damages in rats. Additional two groups were evaluated by administering 0.5 g/kg of the extract to animals either before or after DXR treatment. Kidney function tests were performed by measuring the serum levels of urea, creatinine, uric acid, and total protein. The antioxidant activity of the extract was evaluated by in vivo and in vitro methods. Histopathology of kidney tissues was performed to assess the morphological changes. The significance of results obtained were statistically analyzed. Results: The data obtained indicated that co-administration of the extract at higher doses (0.5 and 1.0 g/kg) significantly (p<0.01) reduces the serum levels of creatinine, urea, uric acid, and total proteins compared to DXR group. The extract also decreases the structural damages induced by DXR and exhibited antioxidant property. However, the pre- and post-treatments of Terminalia extract neither alter significantly the biomarker levels nor ameliorated the histopathological changes induced by DXR in rats. Conclusions: The observations indicated that co-administration of Terminalia chebula decreased the renal damage induced by DXR in rats. The protective action of the extract may be related to its wound-healing and antioxidant properties, the latter of which diminished the free-radical damage induced by DXR.